Lightning performance of covered conductors overhead distribution lines - Thanasaksiri T. (2017)
This paper analyzes the lightning performance of 22 kV, ChiangMai substation 4 to Doi-Suthep, overhead distribution line with covered conductors. The performance of line which related to the insulator flashover has been modeled and analyzed using EMTP. The backflashover rate (BFOR), shielding failure flashover rate (SFFOR) and induced voltage flashover rate (IVFOR) of line have been determined. The number of lightning flashovers from simulation, by applying ground flash density Ng=6.5x10-5Td 2.277, are close with the data from the line outages recorder.